A proposal for developing the performance of administrative leaderships in community colleges and institutes of technical and vocational education in Al Hodeidah Governorate in light of contemporary challenges - Almshraee, Abdulrahman Mahmoud (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the performance of 100 executives working at community colleges, poly-technics, and vocational Institutes in Hodeidah City in light of the contemporary national and international challenges. A proposed framework was attempted to improve their performance. A questionnaire was designed as primary data source of the study. The study adopted the descriptive analytical method. Major findings revealed the following:1- The mean score of the impact ratio of these leading officers with the existing national and international challenges was found to be (3.56 out of 5) with relative weight of (71. 1%) which was considered high. As for main domains, the highest mean scores was found to be one of the existing contemporary challenges both national and international at (3.76) with a relative weight of (75.3%). Then followed by the international challenges domain with a mean score of (3.42) and an impact ratio of (68.4%) and both ratios were considered high. The last domain was of the existing level of the leading officers with a mean score of (3.39) with an impact ratio of (67.8%) which was considered to be average.2- There were significant statistical differences at (0.5) level in the mean scores of the sample according to the following variables: the type of the institution in favor of the poly-technics and according to specialization in favor of other specializations and regarding Community Colleges in favor of the private ones while non-significant differences were found with regard to qualification, years of experience, and the current rank. On the basis of those results, a framework was proposed to improve the performance of those officers working in the previously mentioned institutions in Hodeidah City.
Keywords: Performance Appraisal; Executives; Community Colleges; Vocational Education; Contemporary Challenges; Hodeidah City